5(9x+13)=7(4x+10)

Simple and best practice solution for 5(9x+13)=7(4x+10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(9x+13)=7(4x+10) equation:


Simplifying
5(9x + 13) = 7(4x + 10)

Reorder the terms:
5(13 + 9x) = 7(4x + 10)
(13 * 5 + 9x * 5) = 7(4x + 10)
(65 + 45x) = 7(4x + 10)

Reorder the terms:
65 + 45x = 7(10 + 4x)
65 + 45x = (10 * 7 + 4x * 7)
65 + 45x = (70 + 28x)

Solving
65 + 45x = 70 + 28x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-28x' to each side of the equation.
65 + 45x + -28x = 70 + 28x + -28x

Combine like terms: 45x + -28x = 17x
65 + 17x = 70 + 28x + -28x

Combine like terms: 28x + -28x = 0
65 + 17x = 70 + 0
65 + 17x = 70

Add '-65' to each side of the equation.
65 + -65 + 17x = 70 + -65

Combine like terms: 65 + -65 = 0
0 + 17x = 70 + -65
17x = 70 + -65

Combine like terms: 70 + -65 = 5
17x = 5

Divide each side by '17'.
x = 0.2941176471

Simplifying
x = 0.2941176471

See similar equations:

| -35+7+12-18-1-16= | | 2(6x+14)=7(8x+12) | | 2(x+8)=5(x+11) | | 16=3x-X | | X=27+-1Y | | 6=3y+9 | | 2(x+6)=5(x+12) | | 20-/2=50 | | 1.5x=24 | | 1.5=24 | | 15=300 | | 3p^2-5p+2=y | | ln(X-7)-5=2 | | X+Y+10=37 | | 2/9t=36 | | 3B+4B=24 | | 16-3+-4+2-12+2= | | x^4-tx^2+16=0 | | 121^3/2 | | 10-2f=15-3f | | 5m+4m=27m | | 5y^2+7y-34=0 | | (7x-1)/5=x | | x^2-x/2-(x-4)^2/3≥0 | | 85=6k+5-(k+5) | | 85=6k+4-(k+5) | | 85=6k+4+(k+5) | | a-11=22 | | 85=6k+3-(2k+5) | | YGAF-YGAF= | | 6|4y-3|-2=16 | | 85=6k+3-(k+5) |

Equations solver categories